PENGARUH LIQUIDITY, FOREIGN OWNERSHIP, DAN GOOD CORPORATE GOVERNANCE TERHADAP DIVIDEND POLICY - Kevin Hans Setiawan; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to determine the effect of liquidity, foreign ownership, and Good Corporate Governance on dividend policy on manufacturing companies that listed on Indonesia Stock Exchange on 2017 – 2019. Sample was selected using purposive sampling method and the valid data was 38 companies. Data processing techniques using multiple regression analysis what helped by Eviews 12 program. The result of this study stated that liquidity had a significant effect on dividend policy. While foreign ownershipand Good Corporate Governance didn’t have significant effect on dividend policy. This study also stated that independent variable liquidity, foreign ownership, and Good Corporate Governance simultaneously have a significant effect on dividend policy. The implication of this study is the need to increase company’s liquidity to increase dividend policy on the company.